K-Continuity Is Equivalent To K-Exactness - Uuye, Otgonbayar (MATHEMATICA SCANDINAVICA, 2016)
Let A be a C^*-algebra. It is well known that the functor B A B of taking the minimal tensor product with A preserves inductive limits if and only if it is exact. C^*-algebras with this property play an important role in the structure and finite-dimensional approximation theory of C^*-algebras. We consider a K-theoretic analogue of this result and show that the functor B K_0(A B) preserves inductive limits if and only if it is half-exact.